Penentuan Sistem Kompensasi Berdasarkan Risk Assessment dan Performance Appraisal Karyawan (Studi Kasus: Petugas Operasional Pemadam Kebakaran Kota Padang) - Difana Meilani; Nurmay Rahmah (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2016)
Risk is a possibility of the occurrence that may affect the achievement of objectives. Risk can give positive or negative effect. One of the jobs that have a high risk is firefighter job. Furthermore, a firefighter who are disciplined, responsible, and good in team work, they must be given a reward for their motivation. Therefore, the compensation that they get is equal with the potential risk and working achievement. The compensation of the risk and achievement is included in the extra payment of dangerous work (hazard pay) and bonus based on working achievement of an employee (merit pay). Comparing to the old system, the compensation system will increase the firefighters' income from Rp 900.000 to Rp 1.297.280 every month. The addition will also increase the budget of Damkar from Rp 550.800.000 to Rp 793.935.156 every year.